Program Sekolah Sehat Jiwa (SSJ): Studi Implementasi di SMPN 7 Yogyakarta - Rizna Ayustyawati (Spektrum Analisis Kebijakan Pendidikan, 2025)
This study aims to describe the implementation of the Mental Health School Program (SSJ) in building character and student achievement at SMPN 7 Yogyakarta, and to analyze the supporting and inhibiting factors in its implementation. The method used is a qualitative research with a descriptive approach involving the principal, teachers, and students selected by purposive sampling as research subjects. Data were collected through observation, interviews, and document studies, then analyzed using data collection techniques, data condensation, data presentation, and conclusion drawing. The results of the study indicate that the implementation of SSJ runs well with the support of effective communication, adequate human resources and infrastructure, and the commitment of implementers. The main supporting factors include the presence of competent trainers and teachers, appropriate facilities, stakeholder support, and student enthusiasm. Inhibiting factors are the implementation time and small space. The positive impacts of this program include increased knowledge about mental health, social skills, and a more positive learning environment.